Copper acetate catalysed C–C bond formation en route to the synthesis of spiro indanedione cyclopropylpyrazolones. Issue 18 (19th April 2022) - Penjarla, Thirupathi Reddy; Shukla, Adarash Kumar; Hazra, Rituparna; Roy, Durba; Kundarapu, Maheshwar; Dixit, Mudit; Bhattacharya, Anupam
Abstract : C–C coupling using Cu(OAc)2 as the catalyst for the synthesis of spiro indanedione cyclopropylpyrazolones under an oxygen atmosphere. Abstract : This article reports the synthesis of spiro compounds based on an indanedione–cyclopropane–pyrazolone framework. The reaction relied upon the Michael-initiated ring closure strategy and was carried out under Cu(OAc)2 catalysis, assisted by an oxygen atmosphere and the base Et3 N. The final compounds were obtained as an inseparable mixture in most cases with modest to good yields using diverse substrates. Among the two plausible routes, computational studies indicated the feasibility of a route which involves a four-membered Cu containing intermediate. Given the generic nature of the developed method, it may be utilised to synthesise other analogous spiro systems.